Recruit to Reject? Harvard and African American Applicants - Peter Arcidiacono; Josh Kinsler; Tyler Ransom (Institute of Labor Economics (IZA), 2019)
Over the past 20 years, elite colleges in the US have seen dramatic increases in applications. We provide context for part of this trend using detailed data on Harvard University that was unsealed as part of the SFFA v. Harvard lawsuit. We show that Harvard encourages applications from many students who effectively have no chance of being admitted, and that this is particularly true for African Americans. African American applications soared beginning with the Class of 2009, with the increase driven by those with lower SAT scores. Yet there was little change in the share of admits who were African American. We show that this change in applicant behavior resulted in substantial convergence in the overall admissions rates across races yet no change in the large cross-race differences in admissions rates for high-SAT applicants.
Keywords: I23; I24; 330; college applications; college recruiting; inequality